10+g-3g=26

Simple and best practice solution for 10+g-3g=26 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10+g-3g=26 equation:


Simplifying
10 + g + -3g = 26

Combine like terms: g + -3g = -2g
10 + -2g = 26

Solving
10 + -2g = 26

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-10' to each side of the equation.
10 + -10 + -2g = 26 + -10

Combine like terms: 10 + -10 = 0
0 + -2g = 26 + -10
-2g = 26 + -10

Combine like terms: 26 + -10 = 16
-2g = 16

Divide each side by '-2'.
g = -8

Simplifying
g = -8

See similar equations:

| (2-1x+7)=(x+3+4) | | 3x+2.7=2.7 | | log[5](2x-6)=4 | | 4=5*14-7 | | 0.2x+0.3y=0.5 | | 3y+19=5y-29 | | 1+7x=-17+x | | 18x^1/2 | | 1.125/5=x | | 4t*5t= | | 2=5*3-7 | | 2/3x-5=x+4 | | -4+4x=16+13x | | sin(2t)= | | 3(x+11)+11=2x+47 | | 8x+2=-6+6x+24 | | 400/x=x | | 6-3x-30=3 | | 2.25+3w=-6.75 | | cos(2x)=1+sin(2x) | | 4(x+1)=4(-x+3) | | 10x=3y | | 3(x+2)=x-24 | | -9x-8=4x+18 | | 1.16666666666667/3=x | | 56-5x=11-10x | | 6+30x=15x+24 | | x^2-5x+31=0 | | 17-6x=11-8x | | 12.32b=-7.04 | | 5-(-8+8i)-(-6-i)= | | 12.32b=7.04 |

Equations solver categories